Նիկիայի Բ Տիեզերաժողովի (787 թ․) կանոնները. Միջնադարյան հայերեն թարգմանությունը՝ հունարեն բնագրի հետ զուգորդմամբ - Մելքոնյան, Սարգիս Ռ․
The Second Council of Nicaea, which was held in 787 and recognized by the Orthodox Churches that followed the Byzantine tradition and the Western Church (the Roman Catholic and Protestant Churches separated from it) as the Seventh "Ecumenical Council", is of great significance to the history of the church, not only in terms of the study of the dispute over the treatment of images but also from the point of view of the study of issues of canon law and church administration. The 22 canons promulgated by the Council were strictly administrative and prescriptive in nature compared to the canons of previously held Councils. Most likely, this was connected with the desire to restore the ecclesiastical order shaken by the disputes over the images and after them. Therefore, the respective study of the canons of the Second Council of Nicaea seems important, first of all, from the point of view of canon law. This study aims to publish an Armenian translation of the canons of the Council of Nicaea of 787, most probably made in the 13th–14th centuries, along with the Greek original. Such research is relevant not only as a disclosure of the previously unpublished original Armenian text of the canons, but also in the context of clarifying various canonical-legal and administrative concepts of the church and the study of church Councils.
Keywords: Նիկիայի ժողով